2015
DOI: 10.1523/jneurosci.4696-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Parietal Cortex Encoding of Dynamic Hand Force Underlying Hand-Object Interaction

Abstract: Major achievements of primate evolution are skilled hand-object interaction and tool use, both in part dependent on parietal cortex expansion. We recorded spiking activity from macaque inferior parietal cortex during directional manipulation of an isometric tool, which required the application of hand forces to control a cursor's motion on a screen. In areas PFG/PF, the activity of ϳ70% neurons was modulated by the hand force necessary to implement the desired target motion, reflecting an inverse model, rather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 47 publications
1
14
1
Order By: Relevance
“…The force pattern we observed is also different from the unipolar increases of exerted force during voluntary goal-directed isometric contractions ( Desmedt and Godaux, 1978 ; Ferrari-Toniolo et al, 2015 ). Instead, the alternating patterns of force decreases and increases are reminiscent of the earliest stage of voluntary ballistic movements, when agonists and antagonists muscles alternate bursts of activity to trigger a goal-directed action ( Marsden et al, 1983 ; Berardelli et al, 1996 ).…”
Section: Discussioncontrasting
confidence: 89%
“…The force pattern we observed is also different from the unipolar increases of exerted force during voluntary goal-directed isometric contractions ( Desmedt and Godaux, 1978 ; Ferrari-Toniolo et al, 2015 ). Instead, the alternating patterns of force decreases and increases are reminiscent of the earliest stage of voluntary ballistic movements, when agonists and antagonists muscles alternate bursts of activity to trigger a goal-directed action ( Marsden et al, 1983 ; Berardelli et al, 1996 ).…”
Section: Discussioncontrasting
confidence: 89%
“…PFG is composed of neurons active during the execution of object-oriented hand actions ( Gardner et al, 2007 ; Rozzi et al, 2008 ), often showing selectivity for grip type ( Bonini et al, 2012 ). Concerning hand dynamics, neural activity in PFG encodes instantaneous force variation and retains memory of force signals for guiding hand action ( Ferrari-Toniolo et al, 2015 ). These data suggest an involvement of this area in the cortical network for fine control of object grasping and manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…Real‐time visual cues that point to online changes in the action, such as a curve that went a bit too far to the right while making an ‘R’, may invoke these parietal responses in expert writers who have acquired their own stereotyped movement patterns for each letter as well as a large amount of experience with them. Several recent neurophysiological studies have suggested that the left intraparietal sulcus does, in fact, store some memory of a past experience of visual‐motor coordination (Ferrari‐Toniolo, Visco‐Comandini, Papazachariadis, Caminiti, & Battaglia‐Mayer, 2015; Haar, Donchin, & Dinstein, 2015; Kastner, Chen, Jeong, & Mruczek, 2017), perhaps accumulating evidence for potential motor movements (Tosoni, Galati, Romani, & Corbetta, 2008), and this same region has been associated with visual‐motor coordination during letter production in adults (Haar et al, 2015; Kadmon Harpaz, Flash, & Dinstein, 2014; Vinci‐Booher et al, 2019).…”
Section: Discussionmentioning
confidence: 99%